Islamic social banking : the way forward - M. Luthfi Hamidi; Worthington, Andrew C. (Penerbit Universiti Kebangsaan Malaysia, 2018)
This paper discusses Islamic social banking (ISB). We first critically examine current practice in Islamic banking (IB) and any deviations from core Islamic principles. These can lead to the apparent social failure of IB given that it will then fail to improve on the economic development of ordinary people. We draw comparison with the generally positive contribution of social banking (SB) to be inserted in IB as a means to create a synthesis in the form of ISB. Theoretically, we find IB and SB share similar 3P principles (Profit, Planet, People) in their operations. We extend these principles to another P (for Prophet) to cover the thoughts and guidance of Islam as ethical guidance for ISB to develop framework based on 4P. We suggest an approach to evaluate the social outcomes of ISB and some good SB practices to be considered.